The Craft of Fractional Modelling in Science and Engineering - Jordan Hristov (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book is a result of the contributions of scientists involved in a Special Issue entitled "The Craft of Fractional Modelling in Science and Engineering" published by the journal Fractal and Fractional (MDPI). Most of the articles were published at the end of 2017 and the beginning 2018. In accordance with the initial aim of the Special Issue, the best published have now been consolidated into this book. The articles included span a broad area of applications of fractional calculus and demonstrate the feasibility of the non-integer differentiation and integration approach in modeling, directly related to pertinent problems in science and engineering. This a good beginning and it would be beneficial to continue with this collection under the same title and potentially provide a second volume of this book in the future.